What Do Nectarivorous Bats Like? Nectar Composition in Bromeliaceae With Special Emphasis on Bat-Pollinated Species - Göttlinger, Thomas; Schwerdtfeger, Michael; Tiedge, Kira; Lohaus, Gertrud (Frontiers in Plant Science, 2019)
Floral nectar is the most important reward for pollinators and an integral component of the pollination syndrome. Nectar research has mainly focused on sugars or amino acids, whereas more comprehensive studies on the nectar composition of closely related plant species with different pollination types are rather limited. Nectar composition as well as concentrations of sugars, amino acids, inorganic ions, and organic acids were analyzed for 147 species of Bromeliaceae. This plant family shows a high diversity in terms of floral morphology, flowering time, and predominant pollination types (trochilophilous, trochilophilous/entomophilous, psychophilous, sphingophilous, chiropterophilous). Based on the analyses, we examined the relationship between nectar traits and pollination type in this family. Nectar of all analyzed species contained high amounts of sugars with different proportions of glucose, fructose, and sucrose. The total concentrations of amino acids, inorganic cations and anions, or organic acids were much lower. The analyses revealed that the sugar composition, the concentrations of inorganic cations and anions as well as the concentration of malate in nectar of bat-pollinated species differed significantly from nectar of species with other pollination types. Flowers of bat-pollinated species contained a higher volume of nectar, which results in a total of about 25-fold higher amounts of sugar in bat-pollinated species than in insect-pollinated species. This difference was even higher for amino acids, inorganic anions and cations, and organic acids (between 50 and 100-fold). In general, bat-pollinated plant species invest large amounts of organic and inorganic compounds for their pollinators. Furthermore, statistical analyses reveal that the characteristics of nectar in Bromeliaceae are more strongly determined by the pollinator type rather than by taxonomic groups or phylogenetic relations. However, a considerable part of the variance cannot be explained by either of the variables, which means that additional factors must be responsible for the differences in the nectar composition.